Improving a Centrifugal Compressor's Performance at Low Mass Flow Rates by Adding an Acoustic Resonator - Renz, Andreas; Bär, Katharina; Becker, Stefan (Journal of Engineering For Gas Turbines and Power-Transactions of the Asme, 2023)
Acoustic resonators are widely used to dampen the sound radiation of centrifugal compressors of automobile turbochargers. Their advantages are simplicity, robustness, ease of integration, and acoustic tunability. Interestingly, some resonators mounted to the inlet side improved compressor performance at low mass flow rates significantly. In this paper, this phenomenon was investigated experimentally by an extensive study of resonator geometries on a turbocharger test rig and numerically by uRANSs of selected compressor resonator configurations near the surge limit. A detailed description is given on how the resonator can limit the disturbance of the incoming flow and improve the impeller's operating conditions by ingesting the backflow coming from the blade tips. The backflow's kinetic energy and angular momentum are greatly reduced inside the resonator before the fluid flows back into the inlet duct. Concluding, design guidelines for a resonator geometry, which improve performance as an addition to its acoustic properties, are shared.
CRIS-Team Scopus Importer:2024-12-16